Sjogern - Larsson Syndrome: A Case Report - Karim, Rashidul; Sultana, Humayra; Uddin, Md Sultan (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2015; VOL 39 (2) :102-104